An Analysis of Non-Conventionally Indirect Request in Haikyuu!! (1st Season) Anime - Siti Sumarti; Pratomo Widodo (Journal of English Language Teaching and Linguistics, 2019)
This research is aimed to find and to explain the implicit meaning in non-conventionally indirect request in Haikyuu!! (1st Season) anime and the reason the speaker request in non-conventionally indirect way which found in Haikyuu!! (1st Season) anime. This research is in descriptive qualitative research. The data were taken from Haikyuu!! (1st Season) anime, specifically, the dialogue from the Haikyuu!! (1st Season) anime that contains non-conventionally indirect request. The subject of the research is Haikyuu!! (1st Season) anime and the object is non-conventionally indirect request. In collecting the data, the researcher uses teknik catat or noting technique. In analyzing data, the researcher uses metode padan specifically in metode padan pragmatics. The analysis of the research shows that Haikyuu!! (1st Season) anime, from 25 episodes, has four forms of non-conventionally indirect request in Haikyuu!! (1st Season) anime, they are: imperatives, interrogatives, negative interrogatives, and declaratives.